2006
DOI: 10.1016/s0001-2092(06)60167-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Perioperative Medication Errors With Regard to Organization Characteristics

Abstract: RESEARCHERS CONDUCTED a descriptive, comparative, secondary analysis using a national database to investigate differences in perioperative medication error characteristics with regard to organization characteristics. PERIOPERATIVE MEDICATION ERROR records reported to the MEDMARX database between Sept 1, 1998, and Aug 31, 2003, were examined (N = 5,210), and variables were analyzed using descriptive and inferential statistics. Statistically significant differences were found for three out of four research quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…5 Both MEDMARX database analyses showed administration as the most common cause of error, needing further exploration. In this study, 4 administration (33%) was the most common cause of error followed by documentation/transcription (23%), dispensing (22%), and prescribing (21%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 Both MEDMARX database analyses showed administration as the most common cause of error, needing further exploration. In this study, 4 administration (33%) was the most common cause of error followed by documentation/transcription (23%), dispensing (22%), and prescribing (21%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[1] Moreover, the medication error means a disorder in the treatment process, which is followed by a potential or actual risk of hazard for patient. [2] Nowadays, medication errors have attracted more attention because of the complications like higher mortality rate and cost of health-care.…”
Section: Introductionmentioning
confidence: 99%
“…The top six contributing factors were identified as distraction, inexperienced staff, workload increases, no access to patient information, shift change, and cross coverage. Goeckner et al 14 addressed organizational characteristics related to medication errors in perioperative areas. They found that severity of errors did not vary by type of hospital ownership, but the point in the medication process at which errors occurred did vary according to the size of the hospital.…”
mentioning
confidence: 99%